SAMORZĄD TERYTORIALNY W STANIE EPIDEMII - Naleziński, Bogumił; Holocher, Justyna (Polityka i Społeczeństwo, 2021)
One of the manifestations of the systemic crisis in Poland is progressive centralization in the management of local affairs. The causes of the phenomenon under analysis can be justifiably traced to three factors that are complementary to each other. First, in a constitutional model of the local government which assumes that the legislator has a decisive influence on the scope of tasks entrusted to local government units as well as on the degree of independence of their execution. A consequence of a crisis around the agencies of the third estate is also the weakening of the efficiency of judicial measures of protection of that independence. Secondly, a considerable influence upon the phenomenon under analysis is exerted by the strategy for fighting the pandemic adopted by the public authorities based upon the construction of a ‘hybrid’ state of emergency where the dominant role is played by the central public authorities. Thirdly, further politicization of the local government has become a particular feature of its operation in the times of the pandemic.